Using simulation to help healthcare professionals relaying patient information during telephone conversations. Issue 8 (August 2020) - Petersen, Lene F.; Madsen, Marlene D.; Østergaard, Doris; Dieckmann, Peter
Abstract: Background: The purpose of this paper is to describe a development project in which simulation was used to improve the telephone-based conversations between nurses in an emergency department (ED) and physicians from different specialties taking care of acutely ill patients. Methods: A needs analysis consisting of observations and interviews was conducted and a one-day simulation-based interprofessional team training course was developed. Observations of phone conversations pre-course, three and six months after the course were conducted in the clinical setting with 20 participants in each point of time. A 14-item evaluation tool was used to record how many information pieces were communicated. Results: Five courses were conducted for 66 nurses/nurse assistants and 17 physicians. 9 out of the 14 items were reported significantly more after the course. Item that were not reported in the pre-measurement, increased to around 20% reporting three months after the course but then fell to close to 0% again after six months. Conclusions: The patterns of retention and decrease of the effect could be an indicator for norms, values and beliefs held by professions about what constitutes their task. Abstract : Health profession; Emergency medicine; Intensive care medicine; Organizational psychology; Decision analysis; Conflict resolution; Learning and memory; Hand-over; Simulation; Communication; Coordination; Telephone; Training; Interprofessional collaboration